PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PERTUMBUHAN EKONOMI MELALUI KEMANDIRIAN KEUANGAN DAERAH SEBAGAI VARIABEL INTERVENING DI KABUPATEN INDRAGIRI HULU - Hartika, Dewi; Gustika, Gita Sari (Jurnal Daya Saing, 2026)
This study aims to determine the effect of regional taxes and levies on economic growth through regional financial independence as an intervening variable in Indragiri Hulu Regency from 2015 to 2024. Path analysis was used as the data analysis technique. The results indicate that regional taxes do not affect regional financial independence; regional levies do not affect regional financial independence; regional taxes affect economic growth; regional levies have no effect on economic growth; regional financial independence has no effect on economic growth; regional taxes do not affect economic growth through regional financial independence, and regional levies do not affect economic growth through regional financial independence. Keywords: Economic Growth, Regional Financial Independence, Regional Taxes, Regional Levies